COFOLA International 2019: Private Enforcement of Antitrust Law and Unfair Competition with Cross-border Element (Publications of the Masaryk University, theoretical series, editions Scientia, 2019)
Constitutional Questions about the Directive on Antitrust Damages Action ... : The Rule of Binding Effect of National Competition Authorities’ Decisions Arbitrability of the EU Antitrust Law Consumer Decision Making Process as a Centre of the Marketplace Effects Rule
Keywords: Actes de conférence; Competition law; Concorrência desleal; Concurrence (droit); Concurrence déloyale; Droit de la concurrence; E-knihy; Knihy; Litiges internationaux; Mezinárodní spory; Nekalá soutěž; Právo; Právo hospodářské soutěže; Sborníky konferencí; Čítárna

Resale price maintenance in consumer good markets: an economic justification for the prohibition of RPM - Schwaderer, Melanie Ariane (European University Institute, 2019)
The thesis contributes to the debate on the EU’s approach to the business practice of resale price maintenance (RPM), which is widely criticized as too strict and in conflict with what is considered to be the consensus in the economic literature. The thesis critically dissects the economic consensus, on which the critique against the EU’s approach is based, by analyzing the empirical evidence that is cited to support the claim that RPM can frequently be explained by the service-based RPM models and shows that there is no convincing evidence that would support the significance of these positive RPM models that predict positive effects on welfare. To support this finding the thesis collects new evidence by surveying the marketing literature and shows that not only is there no convincing evidence that the positive RPM models frequently apply, but to the contrary there is evidence that these models are inconsistent with the real world phenomenon of RPM. Having refuted the service-based models the thesis takes up the scientific challenge that “it takes a theory to beat a theory” and proposes to fill the gap with three price-based models. The thesis offers an analysis of the three price-based RPM models, first from the perspective of welfare effects and then from a broader economic perspective in an attempt to ultimately show that the EU approach to RPM can be justified based on these economic models. All three models explain the situation in which RPM is used by a branded good manufacturer to create the perception of high quality, which is used either as a credible quality signal, becomes a component of the product or is used to bias the consumer decision; they thus enter the difficult terrain of consumer preference formation and of markets for the intangible components of a product.
Keywords: Competencia; Competition law; European Union countries; Marketing; Price maintenance

Restraint of trade clauses: does the enforcement thereof promote anti-competitive behaviour in South African law? - Sithole, Mthokozisi Wesley Nhlakanipho (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Anti-competitive behaviour; Business agreements; Competencia; Competition law; Employment agreements; Restraint of trade; Trade clause

Integrating healthcare quality concerns into a competition law analysis : mission impossible? - Stavroulaki, Theodosia (European University Institute, 2017)
Healthcare markets have started being created in Europe. Indeed, some European countries, such as the UK and the Netherlands, have started adopting the choice and competition model for healthcare delivery. Taking as a starting point that as health systems in Europe move towards market driven healthcare delivery, the application of competition law in these systems will increase, the goal of this doctoral thesis is (a) to identify some of the competition problems that may be raised in light of the reality that especially in hospital and medical markets the pursuit of competition and the pursuit of essential dimensions of healthcare quality may inevitably clash (b) to demonstrate that competition authorities would be unable to address some of these competition problems if they did not pose and address a fundamental question first: how should we define and assess quality in healthcare? How should we take healthcare quality into account in the context of a competition analysis? In delving into these questions, this doctoral thesis explores how the notion of healthcare quality is defined from antitrust, health policy and medicine perspectives and identifies three different models under which competition authorities may actually assess how a specific anticompetitive agreement or hospital merger may impact on healthcare quality. These are: (a) the US market approach under which competition authorities may define quality in healthcare strictly as choice, variety, competition and innovation (b) the European approach under which competition authorities may extend the notion of consumer welfare in healthcare so that it encompasses not only the notions of efficiency, choice and innovation, but also the wider objectives and values European health systems in fact pursue (c) the UK model under which competition authorities may cooperate with health authorities when they assess the impact of a specific transaction on healthcare quality. The thesis identifies the main merits and shortcomings of these models and emphasizes that what is crucial for the adoption of a holistic approach to healthcare quality is not only the model under which healthcare quality is actually integrated into a competition analysis but also competition authorities’ commitment to protect all dimensions of this notion.
Keywords: European Union countries; Medical care; Medical laws and legislation; Medical policy; Unfair competition

A critical review of the treatment of dominant firms in competition law : a comparative study - Munyai, Phumudzo S. (University of South Africa, 2016)
In South Africa compliance with competition law has become a major concern for firms that achieve and maintain certain levels of success and growth in the market, as their actions are often a source of complaints and litigation by rivals and competition authorities. With substantial financial penalties often levied against them for a variety of conduct deemed to constitute an abuse of their market position, dominant firms must constantly be aware of the likely impact of their business strategies and actions on both rivals and consumers. What were once thought to be normal and economically sound business practices and decisions, such as cutting prices to attract customers, have now acquired new meanings, with devastating consequences for dominant firms. So, are dominant firms under attack from competition law? In this study I aim to determine this. I track the historical development of competition law in three jurisdictions: South Africa, America, and the EU, with the aim of identifying traces, if any, of hostility towards dominant firms in the origins of competition law. I further investigate whether the formulation and enforcement of certain aspects of existing abuse of dominance provisions manifest as hostility towards dominant firms. While acknowledging the important role that competition law enforcement plays in promoting competition and enhancing consumer welfare, I conclude that significant unjustified economic and legal prejudice is suffered by dominant firms as a result of the way in which certain abuse of dominance provisions have been formulated and applied. I also offer appropriate recommendations.
Keywords: Abuse of dominance; Anti-monopoly; Anticompetitive effects; Anticompetitive harm; Antitrust law; Causation; Competencia; Competition Appeal Court; Competition Commission; Competition Tribunal; Competition law; Consumer harm; Consumer welfare; Counterfactual; Dominant firms; Exclusionary conduct; Hostility; Monopoly; Super-dominant; Unilateral conduct

The Interface Between Competition Law and Intellectual Property Law in Kenya - Jerobon, Rotich Caroline (University of Nairobi, 2016)
The interaction between competition law and intellectual property law has often attracted divergent views from scholars and practitioners of each respective sphere of law. Whereas some argue that the two are in conflict with each other and cannot be reconciled. The aforementioned tension between competition law and intellectual property law has been traced to the objectives of each. On the one hand, intellectual property rights confer upon their owners an exclusive right to behave in a particular way while on the other hand competition law strives to keep markets open. Other scholars have argued that, in real sense and practice, the two are actually not in conflict but rather that they complement each other. The question then becomes, is there really an irreconcilable difference between the two areas of law? This paper seeks to establish how the two aspects of law interact and seeks to propose that there be created a balance to alleviate the perceived conflict between the two. This paper will identify the areas in which the balance can be struck. It will also seek to establish how the Kenyan legislative framework as well as the courts has dealt with the conflict. It will proceed from understanding the goals and objective of both intellectual property law and competition law. This will provide the backdrop against which the alleged conflict originates from. A comparative study with other developed jurisdictions will be undertaken so as to advise on the route that should be taken by Kenya on the interface and a conclusion drawn on how the two areas relate and recommendations drawn from the issues identified in the study made.
Keywords: Competencia; Competition law; Intellectual property

The Regulation of Promotional Competitions in South Africa - Strachan, Daniel Petrus (University of Pretoria, 2016)
Promotional competitions are competitions in which prizes are awarded by lot or chance in order to promote goods or services. Due to the chance element, these competitions are often categorised as lotteries or gambling. Initially, South African legislation did not make provision for the running of promotional competitions, but this situation changed when the Lotteries Act, 1997 came into force. Currently, promotional competitions are regulated by the Consumer Protection Act, 2008 (CPA). This thesis examines the regulation of promotional competitions in South Africa. It commences with a background discussion, which touches on the relevant terminology and some sociological aspects. It then considers the consequences of gambling and the need for and nature of regulation, and deals with the marketing and consumer protection contexts. This is followed by a brief overview of the global and South African history of gambling, lotteries and promotional competitions, which includes a discussion of South African case law. Foreign law relating to promotional competitions in New Zealand and Great Britain is explored in order to compare this to the South African position. This is followed by an examination of the current regulation of promotional competitions in South Africa, including a discussion regarding the interplay between the CPA and the Lotteries Act and a detailed analysis of the CPA’s provisions. The self-regulation of promotional competitions is discussed as well. The concluding chapter of this thesis contains recommended solutions for the problems identified in the analysis of the relevant legislation.
Keywords: Competencia; Competition law; Concurrence (droit); Consumer law; Droit de la consommation

The Economics of tort law applied to Internet intermediaries : example of intellectual property - Lefort, Marine (École nationale supérieure des mines de Paris, 2015)
La responsabilité des intermédiaires d'Internet fait débat dans un univers numérique de plus en plus complexe. Les intermédiaires offrent des services en ligne. Ils créent ou facilitent des transactions entre des parties tierces (hébergement, e-commerce, fournisseurs d'accès…). A la fin des années 1990, un consensus s'est établi sur l'instauration d'une responsabilité limitée pour ces acteurs, dans le but de favoriser leur développement ainsi que celui d'Internet par des externalités croisées. Cependant, l'apparition régulière de nouveaux usages a induit des externalités négatives affectant certains agents économiques. La multiplication récente de décisions de jurisprudence parfois contradictoires, en particulier dans le domaine de la propriété intellectuelle, vient désormais remettre en cause cette exemption. Elle fait naître un risque juridique pour les intermédiaires d'Internet. Ces-derniers doivent alors prendre en compte ce nouveau contexte dans leurs modèles d'affaires. Notre recherche étudie les comportements spécifiques que la responsabilité des intermédiaires d'Internet engendre à travers l'exemple de la propriété intellectuelle. En premier lieu nous décrivons l'évolution historique de cette responsabilité. Nous développons ensuite un modèle théorique simple qui explore l'influence du risque légal dans un contexte de concurrence entre un intermédiaire et un ayant droit du copyright. Enfin nous étendons ce modèle de concurrence aux différents comportements de protection que peuvent choisir les intermédiaires.
Keywords: Competencia; Competition law; Concurrence; Economie du droit; Intellectual property; Intermédiaires d’Internet; Internet; Internet intermediaries; Law and Economics; Propriedade intelectual; Propriété intellectuelle

Essays in competition policy - Khimich, Aleksandra (Université Toulouse 1 Capitole, 2014)
Dommage économique causé par les cartels: une évaluation pour les pays en voie de développement (En collaboration avec Marc IVALDI, L'École d'économie de Toulouse et CEPR et Frédéric JENNY, ESSEC Business School, Paris) : La détection et la sanction des cartels reste toujours d'une grande importance pour les autorités de la concurrence développées en raison d'une compréhension claire de leur danger potentiel, et donc des avantages de leur dissuasion. Néanmoins, les pays en développement ont souvent du mal à créer ou à renforcer leur autorité de la concurrence - l'exécution d'une division antitrust est coûteuse et la preuve à l'appui concernant les avantages potentiels est toujours manquante. Présente étude fournit la preuve quantitative manquante. Elle propose une évaluation du dommage économique total causé par les cartels en termes de chiffre d'affaires affecté par les pratiques collusoires ainsi qu'en termes de profits excessifs des ententes découlant de surcharge des consommateurs. Les résultats suggèrent que le préjudice économique totale estimé en termes de profits excessifs divisés par le PIB correspondant peut atteindre jusqu’à 1%. En outre, comme la probabilité annuelle maximale de découvrir une entente déjà existante est estimée à environ 24%, il est suggéré que le dommage économique réel dépasse nos estimations, au moins quatre fois. / Évaluation de la précision des outils proposés dans les lignes directrices sur les fusions (En collaboration avec Marc Ivaldi, L'École d'économie de Toulouse et CEPR et Jérôme Foncel, EQUIPPE, Université de Lille) : Présente étude propose une évaluation complète de la précision de deux outils proposés par les lignes directrices sur les fusions les plus avancés - le critère traditionnel HHI et un plus récent UPP - et défini les conditions économiques qui favorisent les prédictions trompeuses. Les simulations de Monte-Carlo sont utilisées pour créer des économies qui sont utilisés pour mesurer les effets des fusions et d'évaluer la performance des outils d'évaluation choisis. Les résultats suggèrent que le test HHI à une capacité très faible de déterminer le potentiel de l'augmentation des prix lorsqu'il est appliqué à un marché de produits différenciés. Dans son tour, le test UPP peut aussi être très trompeur, même si l'on a une information parfaite sur les principaux ingrédients nécessaires pour le calculer. L’étude démontre que certains d'erreurs de type I et de type II se produit parce que les tests de type UPP par construction ne tiennent pas compte de la ‘pression’ sur le prix subie par le partenaire de fusion. Elle aussi explique comment ce dernier peut être réglé en tenant compte du degré de transmission croisé correspondant. / Le rôle du degré de transmission croisé dans les évaluations des fusions : Présente étude démontre que l'ignorance de l’effet de transmission croisé, et en particulier de son signe, peut conduire à des conclusions erronées dans presque toutes les étapes d’évaluation d’une fusion, y compris la procédure de définition du marché et l'évaluation des effets coordonnés et unilatéraux. Par conséquent, l’étude aussi offre un examen des propriétés de l'ensemble de la matrice des degrés de transmission dans un cadre suffisamment général et en même temps plus pratique pour les concentrations horizontales et tire les caractéristiques exactes des systèmes d'offre et de demande qui affectent le signe du degré de transmission croisé.
Keywords: Cartels; Competencia; Competition law; Concurrence; Conditions économiques; Droit international; Pays en voie de développement; Politique de la concurrence

The role of competitors in the enforcement of state aid law - Pastor Merchante, Fernando (European University Institute, 2014)
State aid law is made up of rules and procedures whose main characters are the Member States – as the addressees of the norms – and the Commission – as their enforcer. The prominent position of these two actors often overshadows the impact that the administration of the rules on State aid has on private undertakings, be it the beneficiaries of State aids or their competitors. This thesis is concerned with the latter. The aim of the thesis is to assess the extent to which competitors may rely on the rules on State aid to protect themselves against the potentially harmful effects of subsidies and other forms of state, financial assistance to firms. This endeavour raises two challenges. The first challenge is to identify the channels through which competitors may voice their interest in the context of a system of governance to which they are in principle alien. This is the issue of access. The second challenge is assess the likelihood that the Commission shall heed to the concerns voiced by competitors. In other words, the challenge is to gauge the power of influence that competitors may exert through each of these channels. This is the issue of leverage. In order to carry out this inquiry, the thesis scrutinizes the means of redress available to competitors before national courts (“private enforcement”), as well as the opportunities that they have to make their voice heard in the course of the Commission’s procedures (“public enforcement”) – namely, the possibility to lodge complaints, the possibility to participate in the consultation phase of Article 108(2) TFEU and the possibility to seek the judicial review of State aid decisions.
Keywords: Antitrust law; European Union countries; Government aid; Restraint of trade; Subsidies; Unfair Competition

Competition law and standard essential patents : oscillating between protection of patent rights and access to standards - Petrovčič, Urška (European University Institute, 2014)
This thesis explores the way in which EU and U.S. antitrust rules address opportunistic conducts that emerge in the context of standard essential patents (SEPs). The analysis finds that the two systems have very different scopes in addressing those practices: conduct lawful under U.S. antitrust law is condemned by the EU competition law and vice versa. In contrast to other fields of antitrust, the differences between the EU and U.S. approach do not arise from the application of different legal standards, but rather reflect the core divergences in the statutory texts that address unilateral practices. The analysis also shows that both in the European Union and in the United States, competition authorities have tried to increase the scope of competition law—first, by stretching the antitrust doctrines outside established borders, and second, by advocacy measures designed to avoid opportunism related to SEPs. The thesis shows, nonetheless, that both approaches are problematic and a more cautious strategy is needed to avoid the risk of injecting imbalance in the standardization context.
Keywords: Antitrust law; Competencia; Competition law; European Union countries; Patent licenses; Unfair Competition; United States

Intellectual Property Law and Competition Law - Patel, Atul; Panda, Auro Aurobinda; Deo, Akshay; Khettry, Siddhartha; Mathew, Sujith Philip (Journal of International Commercial Law and Technology, 2011)
Competition law and intellectual property rights (IPRs) have evolved historically as two separate systems of law. There is a considerable overlap in the goals of the two systems of law because both are aimed at promoting innovation and economic growth. Yet there are also potential conflicts owing to the means used by each system to promote those goals. IP laws generally offer a right of exclusive use and exploitation to provide a reward to the innovator, to provide an incentive to other innovators and to bring into the public domain innovative information that might otherwise remain trade secrets. Competition authorities regulate near monopolies, mergers and commercial agreements with the aim of maintaining effective competition in markets. This article introduces the concept of IPRs and Competition law. It highlights important areas of conflict between the two laws and also deals with the Indian antitrust law. It concludes by trying to harmonize the conflicts.
Keywords: Competencia; Competition law; Intellectual property